Physical simulation of muscles and bones - Dima, Emanuel; Dima, Corina; Cristea, Dan (Оптико-електронні інформаційно-енергетичні технології, 2009)
This paper presents a model used to animate a 3D facial mesh. The animation is entirely based on a physical system, thus no artistic skills are required to animate a face through morphing or rigging. The facial expressions are the result of the physical interaction between the different components of the system. The focus is on creating structures to accurately represent the muscles and the bones. The physical engine is essentially a massspring system, but it also supports some other types of structures, namely pressure cells and rigid bodies.